Are EFI data valuable? Evidence from the 2022 FIFA World Cup group stage - Wei, Xiaobin; Zhao, Yifan; Chen, Hui; Krustrup, Peter; Randers, Morten B; Chen, Chong (Biology of Sport, 2024)
The 2022 World Cup used new Enhanced Football Intelligence (EFI) data, stoppage time calculation methods and substitution rules that were introduced by FIFA. The aim of this study is to explore the effectiveness of EFI in match analysis and to identify the key indicators that influence the match and provide a reference for coaches’ tactical design and training. Data were derived from the FIFA website, including EFI data for 48 matches at the group stage of the Qatar World Cup. A total of 46 indicators were used for analysis and the average values of the corresponding indicators for the different competition results were used in the analysis to identify the key index that determines the outcome of the competition. Apart from scoring more goals and having more assists, winning teams had significantly more attempts on target than drawing and losing teams ( p < 0.05); Winning teams had significantly more attempts inside the penalty area, completed defensive line breaks and receptions behind the defensive line than losing teams ( p < 0.05). There is no difference in possession between matches with different results ( p > 0.05). Goals were significantly correlated with completed defensive line breaks and receptions behind the defensive line ( r = 0.27–0.30, p < 0.01). Attempts on target was significantly positively correlated with receptions, final third entries and line breaks ( r = 0.31–0.67, p < 0.01) and negatively correlated with defensive pressures applied ( r = -0.35, p < 0.01). The efficiency of the offense is more important. Teams need to have more receptions, final third entries and line breaks to get more shots on target rather than possession. This study may help coaches to interpret the game from a multi-dimensional perspective and coaches can use EFI to help their teams improve their match performance.